Plant proteome changes under abiotic stress--contribution of proteomics studies to understanding plant stress response - Kosová, Klára; Vítámvás, Pavel; Prášil, Ilja Tom; Renaut, Jenny (Journal of proteomics, 2011)
Plant acclimation to stress is associated with profound changes in proteome composition. Since proteins are directly involved in plant stress response, proteomics studies can significantly contribute to unravel the possible relationships between protein abundance and plant stress acclimation. In this review, proteomics studies dealing with plant response to a broad range of abiotic stress factors--cold, heat, drought, waterlogging, salinity, ozone treatment, hypoxia and anoxia, herbicide treatments, inadequate or excessive light conditions, disbalances in mineral nutrition, enhanced concentrations of heavy metals, radioactivity and mechanical wounding are discussed. Most studies have been carried out on model plants Arabidopsis thaliana and rice due to large protein sequence databases available; however, the variety of plant species used for proteomics analyses is rapidly increasing. Protein response pathways shared by different plant species under various stress conditions (glycolytic pathway, enzymes of ascorbate-glutathione cycle, accumulation of LEA proteins) as well as pathways unique to a given stress are discussed. Results from proteomics studies are interpreted with respect to physiological factors determining plant stress response. In conclusion, examples of application of proteomics studies in search for protein markers underlying phenotypic variation in physiological parameters associated with plant stress tolerance are given.
Keywords: Stress, Physiological; posttranslační úpravy proteinů; herbicidy; vysoká teplota; proteom; Droughts; rýže (rod); Hot Temperature; Proteome; období sucha; Plant Proteins; Oryza; Protein Processing, Post-Translational; stanovení celkové genové exprese; Cold Temperature; rostliny; rostlinné proteiny; fyziologický stres; těžké kovy; Plants; Arabidopsis; nízká teplota; Metals, Heavy; Herbicides; Gene Expression Profiling